Docência universitária na percepção dos professores de uma universidade pública no Brasil e na Argentina - Maria Jose Batista Pinto (2014)
The parameters to this research are set within the higher education context, specifically higher education in the public university under influence of public policies and contemporary social transformations, in order to understand theteachers perception over university teaching in its configurations in a public university in two Latin American countries: Brazil and Argentina. Universitary teaching is understood as every activity performed by teachers in the scope of higher education in universities and inserted into the broad universe of the profession of teaching. With that concept in sight, this work uses as references university and teaching historical and socio-cultural developments in the Western world; theoretical production about the professionalization of teaching underlining its approaching methods and inherent concepts such as: profession, professionalization and professionalism and lastly, the historical and sociopolitical higher education context in Brazil and Argentina. The methodology relies on social-historical comparative research as proposed by Nóvoa (1995b). Odontology, Education and Engineering teachers from public universities in Brazil and Argentina were analyzed through surveys, interviews and observations. The collected data were processed by means of content analysis and descriptiv estatistics. The analysis of the activities taken on by teacher sin the AR and BR universitie sin relation to socio-demographic and economic profile, training and professional career, functional status and working conditions showed significant contrasts between the teachers of each university, allowing us to consider that they reflected the forms within which universitary teaching was regulated in each country, and that among university teachers from the BR university, conditions of professional establishment prevailed over AR university teachers. By analyzing the perceptions of teachers on universitary teaching, weve mapped the following dimensions that characterized the ways teaching is perceived: working conditions, formation, joy from teaching activities and social engagement. By comparing these dimensions between groups, weve found that the teachers perception is influenced by working conditions, being predominant among AR university teachers the perception of teaching as a residual and additional professional activity, and among the BR teachers, the perception of teaching as a stable work and means of improving their professional career. Finally, we believe that the professionalization is influenced by the social-historical context in which it operates and the differences and similarities between the perceptions and the settings of teaching in a public university in Brazil and Argentina brought unique aspects of professionalism related to politic options for higher education in both countries. The study of universitary teaching presents it self as relevant to understand the tensions, dilemmas and contradictions that permeate the social-political choices in the construction of the right to education in each country, as the understanding of their professionalism allows us to identify elements of major or minor adhesion to the Idea of teaching as a symbol of professional status.